Noble Character for the Golden Generation: Islamic Education from the Film Nussa and Rara - Afifah Salsa Bella (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The film Nussa and Rara can be one of the animated films that raises the theme of Islamic teachings and is suitable for early childhood in depicting how to instill commendable morals in children. Therefore, what needs to be examined in this research is the message and meaning in the Nussa and Rara films in helping to form commendable morals for young children. The research method used in this research is library research. The data sources used consist of primary data sources, namely the film Nussa and Rara with the episodes Smile is Charity, Learn Sincerely, Don't Be Arrogant, Tolerance, My Neighbor is Great, Keep the Trust Part 1 and Keep the Trust Part 2. And the secondary data source is in the form of books books, journals and literature that strengthen opinions and complement research results. Data collection techniques in this research are documentation and observation. And the data analysis technique used is content analysis. The results of this research are the values of Islamic education included in the formation of commendable morals in early childhood in the films Nussa and Rara. The value of moral education which includes morals towards Allah SWT, morals towards the Messenger of Allah and morals towards humans are contained in the Nussa and Rara films.